2009
DOI: 10.3181/0902-rm-50
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Glucose Uptake in Mesangial Cells Stimulated by High Glucose: Role of Angiotensin II and Insulin

Abstract: Mesangial cells (MCs) play a central role in the pathogenesis of diabetic nephropathy (DN). MC dysfunction arises from excessive glucose uptake through insulin-independent glucose transporter (GLUT1). The role of the insulin-dependent transporter (GLUT4) remains unknown. This study evaluated the effect of high glucose on GLUT1, GLUT4, and fibronectin expression levels. Glucose uptake was determined in the absence and presence of insulin. Angiotensin II has been implicated as a mediator of MC abnormalities in D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…It has been reported that GLUT4 expression can be regulated in a glucose-dependent manner (2,13). For example, in rats with induced diabetes, circulating glucose increases and GLUT4 mRNA levels are markedly decreased in fat cells and skeletal muscle cells (18).…”
Section: Hcmv Infection Causes Reduced Glut1 Expression and Increasedmentioning
confidence: 99%
“…It has been reported that GLUT4 expression can be regulated in a glucose-dependent manner (2,13). For example, in rats with induced diabetes, circulating glucose increases and GLUT4 mRNA levels are markedly decreased in fat cells and skeletal muscle cells (18).…”
Section: Hcmv Infection Causes Reduced Glut1 Expression and Increasedmentioning
confidence: 99%
“…Furthermore, in 2010, Wang et al [11] linked GLUT1 expression and mesangial cell stretch to VEGF production and an associated increase in matrix protein synthesis, providing an additional conduit for Ang II induction of both GLUT1 and matrix protein synthesis. Finally, studies with ramipril in vivo and losartan in vitro have indicated that inhibition of angiotensin-converting enzyme or angiotensin receptor-1 can suppress renal cortical GLUT1 [41] and mesangial glucose uptake [42], respectively. Ramipril reduced renal cortical angiotensin-converting enzyme activity and GLUT1 expression in diabetic, hypertensive rats [41], while losartan blunted the effects of high glucose on mesangial cell GLUT1, GLUT4, glucose uptake and fibronectin expression [42].…”
Section: Pro-sclerotic Mediators Of Diabetic Nephropathy and Glut1mentioning
confidence: 99%
“…Finally, studies with ramipril in vivo and losartan in vitro have indicated that inhibition of angiotensin-converting enzyme or angiotensin receptor-1 can suppress renal cortical GLUT1 [41] and mesangial glucose uptake [42], respectively. Ramipril reduced renal cortical angiotensin-converting enzyme activity and GLUT1 expression in diabetic, hypertensive rats [41], while losartan blunted the effects of high glucose on mesangial cell GLUT1, GLUT4, glucose uptake and fibronectin expression [42]. These data suggested potential protective effects of the drugs via these mechanisms against progression of diabetic nephropathy.…”
Section: Pro-sclerotic Mediators Of Diabetic Nephropathy and Glut1mentioning
confidence: 99%
“…15 In the present study, we confirmed previous results indicating that MCs exposed to a high-glucose environment exhibit increased local production of AngII, 7 upregulated (P)RR expression, increased ERK1/2 phosphorylation 11 and increased fibronectin production. 16 We also showed that the ERK1/2 phosphorylation and fibronectin overproduction induced by high glucose were decreased by both losartan and (P)RR siRNA, which distinguished between the (P)RR effects that are dependent on and those that are independent of AngII. In contrast to losartan, however, (P)RR siRNA also significantly reduced ERK mRNA and protein levels, resulting in undetectable levels of the phosphorylated forms of ERK1/2 in most of the samples treated with (P)RR siRNA.…”
Section: Discussionmentioning
confidence: 64%